Contemporary tall residential timber buildings: what are the main architectural and structural design considerations? - Ilgın, Hüseyin Emre; Karjalainen, Markku; Pelsmakers, Sofie (International Journal of Building Pathology and Adaptation, 2023)
PurposeThis study examined data from 13 international tall residential timber building case studies to increase our understanding of the emerging global trends.Design/methodology/approachData were collected through literature surveys and case studies to examine the architectural, structural and constructional points of view to contribute to knowledge about the increasing high-rise timber constructions globally.FindingsThe main findings of this study indicated that: (1) central cores were the most preferred type 10 of core arrangements; (2) frequent use of prismatic forms with rectilinear plans and regular extrusions were identified; (3) the floor-to-floor heights range between 2.81 and 3.30 m with an average of 3 m; (4) the dominance of massive timber use over hybrid construction was observed; (5) the most used structural system was the shear wall system; (6) generally, fire resistance in primary and secondary structural elements exceeded the minimum values specified in the building codes; (7) the reference sound insulation values used for airborne and impact sounds had an average of 50 and 56 dB, respectively.Originality/valueThere is no study in the literature that comprehensively examines the main architectural and structural design considerations of contemporary tall residential timber buildings.